Groundwater cyclopoid copepods of peninsular India, with description of eight new species - Totakura, Venkateswara Rao; Reddy, Yenumula Ranga (Zootaxa, 2015)
To date, only three stygobiotic cyclopoid species are known from India: Haplocyclops (Kiefercyclops) fiersi Karanovic & Ranga Reddy, 2005 and Rybocyclops dussarti Ranga Reddy & Defaye, 2008, from bores, and Allocyclopina inopinata Defaye & Ranga Reddy, 2008, from brackish conditions of a hyporheic habitat. Analysis of numerous groundwater samples collected during 2008–2013 from the hyporheic and phreatic habitats in the coastal deltaic belt of the Rivers Krishna and Godavari in Andhra Pradesh state, southeastern India, has shown ten stygobiotic cyclopoid species, of which eight are new to science: Anzcyclops indicus n. sp., Brevicyclops asetosus n. g., n. sp., Brevicyclops brevisetosus n. g., n. sp., Brevicyclops viduus n. g., n. sp., Halicyclops martinezi n. sp., Haplocyclops (Kiefercyclops) godavari n. sp., Haplocyclops (Kiefercyclops) primitivus n. sp., and Rybocyclops defayeae n. sp. All these species are formally described and illustrated herein. Allocyclopina inopinata, which perfectly agrees with its original account, is also recorded in several localities besides its type locality. The heretofore incompletely characterised Paracyclopina orientalis (Lindberg, 1941) is redescribed. A new cyclopid genus, Brevicyclops n. g., is established for three aforementioned new species. Its most diagnostic synapomorphy is the extreme reduction or complete absence of the principal outer apical seta of caudal ramus. So far, the cosmopolitan genus Halicyclops Norman, 1903, is known by six species in India, all from the surface environments. Now, a new species, H. martinezi n. sp., is described from an interstitial hyporheic habitat, and an identification key given for all the Indian species. The genus Anzcyclops Karanovic, Eberhard & Murdoch, 2011, which has hitherto been known from the Western Australia and New Zealand, is discovered in this study. A new species, Anzcyclops indicus n. sp., which has a close relationship with its Western Australian congeners, is described. A brief note on the biogeography of the Indian stygobiotic crustaceans is also added.